The 'unconventionality' of Jesus from the perspective of a diverse audience - Strijdom, J. (Neotestamentica, 1995)
In this article it is argued that Crossan's characterisation of Jesus' intention as 'unconventional' needs refinement, once one considers the 'different' perspectives from which his diverse audience may typically have viewed his words and deeds. Three examples are selected to explicate my thesis: the parable of 'The Good Samaritan', the 'healing' of a leper, and Jesus' table fellowship. In each case it is shown that other scholars have 'sensed' the problem I am addressing, but without expounding it systematically. In conclusion I maintain that Crossan's analysis of the earliest passion traditions presupposes that Jesus had very learned followers in his original movement, an assertion which actually forces us to take the diversity of his first audience very seriously.